Application of a Modified Quantum-behaved Particle Swarm Optimization Algorithm for MPPT - Huang, Ronggeng (Journal of physics. Conference series, 2023)
Aiming at the characteristics of multiple power peaks of the photovoltaic array under non-homogeneous irradiance conditions, a modified quantum-behaved particle swarm optimization algorithm (MQPSOA) for maximum power point (MPP) tracking is provided. The MQPSOA directly controls the duty ratio and dynamically adjusts parameters during its operation. The final results of the photovoltaic system experiment illustrate that the MQPSOA exhibits good performance in the global search of the MPP. It has a fast search rate and small power fluctuation in comparison with particle swarm optimization.